Erythema of Rosacea Impairs Health-Related Quality of Life: Results of a Meta-analysis. Issue 2 (June 2016) - Bewley, Anthony; Fowler, Joseph; Schöfer, Helmut; Kerrouche, Nabil; Rives, Vincent
Abstract Introduction The central diagnostic feature of rosacea is diffuse central-facial erythema. The objective was to summarize published and unpublished health-related quality of life (HRQoL) data from seven previous studies in rosacea patients. Methods A meta-analysis was performed on baseline HRQoL data of subjects with erythema of rosacea from five randomized controlled trials, one open-label safety study and one epidemiological study. The data from four questionnaires were analyzed, including the Euro QoL 5-dimension (EQ5D) generic questionnaire, the Dermatology Life Quality Index (DLQI) dermatology-specific quality of life instrument, the Productivity and Social Life Questionnaire and the Facial Redness Questionnaire. Results The global EQ5D index score was 0.859 and the domains of pain/discomfort (31.5% moderate or extreme pain) and anxiety/depression (26.4% moderate or extreme) were most affected. Worse scores were observed with erythema of rosacea in the absence of inflammatory lesions (EQ5D score of 0.832 for no lesions vs 0.919 for subjects with ≥1 lesion). Almost half (43%) the subjects had at least moderately impaired HRQoL, including 19.8% with a DLQI total score of ≥11 indicating severely impaired HRQoL; symptoms/feelings was the most affected domain. Subjects with a patient self-assessment (PSA) of severe erythema of rosacea had a worse mean DLQI score than moderate PSA subjects (8.6 vs 6.0). Work life and social life were affected, especially in subjects with severe PSA (62% with social life at least somewhat affected). Conclusion Erythema of rosacea causes a marked decrease in HRQoL in most patients, especially those with self-perceived severe erythema and without inflammatory lesions, and should thus be considered as an important medical problem requiring medical intervention. Funding Galderma UK.